Shear Bond Strength of Orthodontic Brackets Bonded to Zirconium Crowns - Blerim Mehmeti; Bleron Azizi; Jeta Kelmendi; Donika Iljazi-Shahiqi; Željko Alar; Sandra Anić-Milošević (Acta Stomatologica Croatica, 2017)
An increasing demand for esthetic restorations has resulted in an increased use of all-ceramic restorations, such as zirconium. However, one of the challenges the orthodontist must be willing to face is how to increase bond strength between the brackets and various ceramic restorations. Bond strength can be affected by bracket type, by the material that brackets are made of, and their base surface design or retention mode. The aim of this study was to perform a comparative analysis of the shear bond strength (SBS) of metallic and ceramic orthodontic brackets bonded to all-zirconium ceramic surfaces used for prosthetic restorations, and also to evaluate the fracture mode of these two types of orthodontic brackets. Material and methods: Twenty samples/semi-crowns of all-zirconium ceramic, on which orthodontic brackets were bonded, 10 metallic and 10 ceramic polycrystalline brackets, were prepared for this research. SBS has been tested by Universal Testing Machine, with a load applied using a knife edged rod moving at a fixed rate of 1 mm/min, until failure occurred. The force required to debond the brackets was recorded in Newton, then SBS was calculated to MPa. In addition, the samples were analyzed using a digital camera magnifier to determine Adhesive Remnant Index (ARI). Statistical data were processed using t-test, and the level of significance was set at α = 0.05. Results: Higher shear bond strength values were observed in metallic brackets bonded to zirconium crowns compared to those of ceramic brackets, with a significant difference. During the test, two of the ceramic brackets were partially or totally damaged. Conclusion: Metallic brackets, compared to ceramic polycrystalline brackets, seemed to create stronger adhesion with all-zirconium surfaces due to their better retention mode. Also, ceramic brackets showed higher fragility during debonding.